Variação sazonal e intelectual na dinâmica populacional de marsupiais e roedores em um mosaico de savana e floresta semidecídua no extremo norte da Mata Atlântica - Souza, Clarice Vieira de (2017)
Populations change through time as consequence of variations in the rates of deaths, births, and migration. Seasonal and inter-annual population fluctuations are associated with endogenous and climatic factors. In order to investigate the seasonality and the effect of endogenous and exogenous factors upon the population dynamics of small mammals, we used data from a capture-mark-recapture study about rodents and marsupials in a mosaic of savanna and forest at the northern tip of the Brazilian Atlantic Forest. The size, density and biomass of the marsupial populations were seasonal. However, this pattern was not observed for the rodents. Small mammal populations were more strongly correlated to the climatic variables of precipitation and evapotranspiration rate with two and six months lags. The survival of D. albiventris was strongly affected by ENSO and the population was regulated by a negative feedback mechanism. Marmosa murina was weakly affected by the climatic factors. Its population dynamics was mainly determined by a positive feedback and by the effect of D. albiventris population. Our results confirm that neotropical marsupials presents a seasonal population dynamics and they are affected by endogenous and climatic factors. However, the ecological differences, interactions between species and environmental type could drive to distinct responses of the species.